Perspectives on Religious Exclusivism in Generation Z by Age Group - Khansa Meradaputhi; Nandang Budiman; Sardin (al-Afkar, Journal For Islamic Studies, 2026)
The growth of information and communication technology currently raises opportunities and challenges, especially for Generation Z. One of the issues that arises is religious exclusivism, which means the tendency to see a particular religion as the only truth and way of salvation, accompanied by an attitude of rejecting or marginalizing the existence of beliefs. other. This research aims to find out the perspective of religious exclusivism in Generation Z based on age group. This research uses a quantitative approach by collecting data using the religious exclusivism instrument (Sukmayadi, 2024). The sample for this research consisted of 100 Generation Z who live in West Java, and used data collection techniques via Google Form, and processed with IBM SPSS 25.0. The results of the study show that there is no significant difference in religious exclusivism between those aged 17 - 21 years and those aged 22 - 26 years. Apart from that, it can be concluded that overall, the sample in this study has a religious exclusivism perspective which is dominated by the medium category. This reflects that generation Z is still in the process of an identity crisis because they still have to fulfill their developmental tasks.